Influence of Salinity and Temperature Gradients on the Variability of the North Brazil Undercurrent - Liu, Hao; Wei, Zexun; Richter, Ingo; Nie, Xunwei; Li, Chuanshun (Frontiers in Marine Science, 2021)
The North Brazil Undercurrent (NBUC) is a narrow (<1°) northward western boundary current in the tropical South Atlantic Ocean. It carries a large volume of water (>16 Sv) and plays an important role in the Atlantic Meridional Overturning Circulation and the South Atlantic Subtropical Cell. Strong salinity and temperature fronts occur over the NBUC region. The role of temperature and salinity gradients on the genesis of NBUC variability has never been explored. This study uses three high-resolution (≤0.1°) and one low-resolution (=0.25°) model outputs to explore the linear trend of NBUC transport and its variability on annual and interannual time scales. We find that the linear trend and interannual variability of the geostrophic NBUC transport show large discrepancies among the datasets. Thus, the linear trend and variability of the geostrophic NBUC are associated with model configuration. We also find that the relative contributions of salinity and temperature gradients to the geostrophic shear of the NBUC are not model dependent. Salinity-based and temperature-based geostrophic NBUC transports tend to be opposite-signed on all time scales. Despite the limited salinity and temperature profiles, the model results are consistent with the in-situ observations on the annual cycle and interannual time scales. This study shows the relationship of salinity-based and temperature-based geostrophic NBUC variations in the annual and interannual variability and trend among different models and highlights the equal important roles of temperature and salinity in driving the variability of NBUC transport.